Feasibility Test of A Testing Station Trainer Situated in Virtual Reality Integrates Computational Thinking Concepts - Didik Hariyanto; Nurhening Yuniarti; Ilmawan Mustaqim; Amelia Fauziah Husna; Andik Asmara; Rohjai Badarudin; Liu Wei-Te (JETL (Journal of Education, Teaching and Learning), 2024)
This research focuses on integrating the Computational Thinking (CT) concept of automation system in vocational education to address the high costs and scarcity of educational resources in practical learning. The rapid industrial expansion of automation, particularly in Modular Production Systems (MPS), necessitates that students grasp both the components' functionalities and operational principles. Another point that needs to be considered is the integrated CT concept in the learning process. The CT for 21st-century skills, this research aims to facilitate knowledge absorption through systematic problem-solving strategies. To reduce cost and scarcity, this research developed an Interactive Virtual Reality Testing Station (IVRTS) employing a CT methodology to replicate MPS functions effectively in a Flexible Manufacturing System (FMS) Laboratory setting. Developing an Interactive Virtual Reality Testing Station (IVRTS) with a CT approach to simulate the working process is expected to overcome this problem in the Flexible Manufacturing System (FMS) Laboratory. The research procedure adopted from Lee Owens' ADDIE development procedure aims to create a CT-based IVRTS as an innovative educational tool. Experimental validation will compare the efficacy of CT-enhanced IVRTS against traditional methods among 36 students from higher schools. Based on the results of research on the IVRTS indicates its significant potential, receiving mainly "Good/Worth It" feedback. Despite the overall positive reception, users reported issues regarding its complex nature and the necessity for ongoing technical support. Refinements to make the system more intuitive and autonomous by streamlining the interface and clarifying functions are essential for broader user adoption.